Prevalence of Sexually Transmitted Diseases in Juvenile Prostitutes and Street Youth - Antonietta Caffaro Rouget; Jean K Mah; Reuben A Lang; Michel R Joffres (Canadian Journal of Infectious Diseases)
Four groups of adolescents – 35 juvenile prostitutes, 36 street youth, 31 monogamous sexually active adolescents and 35 non-sexually active adolescents – were studied between January 1, 1988 and December 31, 1988 for the presence of sexually transmitted diseases and other genital pathogens. The high prevalence of sexually transmitted diseases found in the juvenile prostitutes (Neisseria gonorrhoeae, 49%; Chlamydia trachomatis, 83%) is in contrast to other studies, which document much lower rates of infection. This could be due to the fact that there are few studies done on juvenile prostitutes as a well defined group. Despite high risk sexual behaviour, the consistent use of contraception was low. No contraceptives were used by 57% of the juvenile prostitutes and 85% of the street youth. None of the adolescents sought medical attention although 48% of the juvenile prostitutes and 53% of the street youth had genital symptoms. It appears that the present public health education and health care delivery do not reach this high risk population.